Hantaviruses: An Overview - Simmons, Joe H.; Riley, Lela K. (Comparative medicine, 2002)
Hantaviruses are a newly emerging group of rodent-borne viruses that have significant zoonotic potential. Human infection by hantaviruses can result in profound morbidity and mortality, with death rates as high as 50%, and potentially long-term cardiovascular consequences. Hantaviruses are carried by peridomestic and wild rodents worldwide and have occasionally been linked to infections in laboratory rodents. Because these viruses have been associated with significant human disease, they have become the subject of intense scientific investigation. In this review the reader is introduced to the hantaviruses, including hantavirus diseases and their pathogenesis. A review of the biology, morphology, and molecular biology of the hantaviruses with a brief overview of the ecology and biology of hantavirus-rodent pairs is also included. The risks of occupational exposure to hantaviruses, diagnosis of hantavirus infections, and methods for handling potentially infected rodents and tissues are discussed as well.